2008
DOI: 10.1103/physrevb.77.195419
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between experimental surface data and bulk structure models for quasicrystalline AlPdMn: Average atomic densities and chemical compositions

Abstract: We have examined bulk structure models for icosahedral AlPdMn in terms of the densities, compositions, and interplanar spacings for the fivefold planes that might represent physical surface terminations. We focus on four models that contain no partial or mixed occupancies, but some comparison is made to a fifth model containing such sites. Each of the four models contains paired planes (layers) that can be separated into two main families on the basis of three features: the relative densities of the two planes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 57 publications
(95 reference statements)
2
27
0
1
Order By: Relevance
“…Previous studies have shown that although quasicrystal surfaces, like periodic crystalline surfaces, show atomic steps and thus expose different termination planes, these terminating planes have been found to be self-similar, and not random [29,30]. In the particular experiment described here, there is no uncertainty in the height of the adsorbate atoms above the surface because the structure of this quasicrystal is periodic perpendicular to the surface.…”
mentioning
confidence: 64%
“…Previous studies have shown that although quasicrystal surfaces, like periodic crystalline surfaces, show atomic steps and thus expose different termination planes, these terminating planes have been found to be self-similar, and not random [29,30]. In the particular experiment described here, there is no uncertainty in the height of the adsorbate atoms above the surface because the structure of this quasicrystal is periodic perpendicular to the surface.…”
mentioning
confidence: 64%
“…This surface [73][74][75] provides a quasiperiodic arrangement of local adsorption sites for Ag [68,69,71,73]. No two sites are exactly equivalent although similar motifs repeat quasiperiodically.…”
Section: Ag On 5-f I-al-pd-mn: Partial Propagation Of Quasicrystallinmentioning
confidence: 99%
“…This height selection is again attributed to QSE, as discussed further below. In the quasicrystalline substrate, different "layers" of atoms actually consist of a few vertically-closely-spaced planes of atoms, with the top layer being Alrich [73,74]. Likewise, the 3D Ag islands presumably consist of such "layers" with a selected height of 3 layers.…”
Section: Ag On 5-f I-al-pd-mn: Partial Propagation Of Quasicrystallinmentioning
confidence: 99%
“…This chemical composition has also been confirmed experimentally. 31 The centers of the D tiles can be occupied Alternatively, the structure of the surface can be described by a -scaled P1 tiling Fig. 2͑a͒ shows the P1 and the P1 tiling and their relation to the DHBS.…”
Section: B Structure Of the Clean Fivefold Surface Of Al-pd-mnmentioning
confidence: 99%